Towards the new energy storage system for conventional cars - Sladić, Saša (Array, 2018)
Lead-acid batteries are widely used in conventional cars. This electric energy storage system (ESS) has to be capable to store enough energy for cranking the conventional car after the weeks without additional charging. After the start of internal combustion engine (ICE) of conventional car synchronous machine usually called alternator start to generate electrical energy. Electric current supplied in this way should be rectified and stored in lead-acid battery for the next start-up. In this article a model of whole process was developed and simulated. Particularly, a supercapacitors were compared with lead-acid batteries and other battery types in sense of mass, reliability and other parameters. Results were confirmed by measurement on conventional car. Furthermore, possibility of replacement of lead-acid batteries with supercapacitors was analyzed.